Behavioral Patterns in Special Education. Good Teaching Practices - Rodríguez-Dorta, Manuela; Borges, África (Frontiers in Psychology, 2017)
Providing quality education means to respond to the diversity in the classroom. The teacher is a key figure in responding to the various educational needs presented by students. Specifically, special education professionals are of great importance as they are the ones who lend their support to regular classroom teachers and offer specialized educational assistance to students who require it. Therefore, special education is different from what takes place in the regular classroom, demanding greater commitment by the teacher. There are certain behaviors, considered good teaching practices, which teachers have always been connected with to achieve good teaching and good learning. To ensure that these teachers are carrying out their educational work properly it is necessary to evaluate. This means having appropriate instruments. The Observational Protocol for Teaching Functions in Primary School and Special Education (PROFUNDO-EPE, v.3., in Spanish) allows to capture behaviors from these professionals and behavioral patterns that correspond to good teaching practices. This study evaluates the behavior of two special education teachers who work with students from different educational stages and educational needs. It reveals that the analyzed teachers adapt their behavior according the needs and characteristics of their students to the students responding more adequately to the needs presented by the students and showing good teaching practices. The patterns obtained indicate that they offer support, help and clear guidelines to perform the tasks. They motivate them toward learning by providing positive feedback and they check that students have properly assimilated the contents through questions or non-verbal supervision. Also, they provide a safe and reliable climate for learning.